Navigation and 3D-imaging in pelvic ring surgery: a systematic review of prospective comparative studies - Boudissa, Mehdi; Khoury, Georges; Franke, Jochen; Gänsslen, Axel; Tonetti, Jérôme (Archives of orthopaedic and trauma surgery, 2024)
Few literature reviews have been published focusing on navigation, robotic or pre-operative planning using 3D-imaging technology (3D-printing, 3D-planning). To our knowledge, no reviews have been performed to assess and compare all these modalities together versus control groups (conventional fluoroscopy) through high Randomized Control Trials (RCTs) and Prospective Control Studies (PCSs). The aim of this study was to assess and compare 3D-imaging technologies from pre-operative planning to per-operative navigation and robotic in the management of pelvic ring fractures through high level studies.
Gesehen am 04.02.2025